Poverty - Senker, Cath. (London : Franklin Watts, 2008)
Presents a brief study of the causes of poverty around the world and the efforts by the United Nations to fund aid programs and provide education and basic needs to countries with the most severe problems.
Patterns of poverty -- Poverty and health -- Getting an education -- Environment and resources -- Global trade -- The burden of debt -- Aid and development -- What if we act now?
Includes bibliographical references (p. 47) and index.
Booklist
Wilson's Children
Wilson's Junior High School
8.9
5-8.
Keywords: Poor -- Education -- Juvenile literature; Poor -- Health and hygiene -- Juvenile literature; Poverty -- Juvenile literature; Poverty -- Prevention -- Juvenile literature; Poor -- Education; Poor -- Health and hygiene; Poverty; Poverty -- Prevention; Poor -- Education; Poor -- Health and hygiene; Poverty; Poverty -- Prevention